New‐Occurrence of Postoperative Modic Changes and Its Influence on the Surgical Prognosis After Percutaneous Endoscopic Lumbar Disc Discectomy - Lei Li; Chao Wang; Hao Zhang; Zhiming Liu; Zheng Lian; Han Li; Hao Tao; Xuexiao Ma (Orthopaedic Surgery)
ABSTRACT Objectives Lumbar disc herniation (LDH) is a common degenerative spinal disease in clinical practice. This study aims to investigate the impact of Modic changes (MCs) on postoperative recovery and disease recurrence following percutaneous endoscopic lumbar disc discectomy (PELD), providing important insights for improving the management of chronic low back pain. This study investigates the 1‐year progression rate of MCs after PELD and their impact on surgical outcomes and recurrence. Methods This retrospective cohort study analyzed data from 419 patients with single‐segment lumbar disc herniation who underwent PELD between January 2019 and December 2022. Lumbar MRI assessed preoperative and postoperative MCs. Pain levels and surgical outcomes were evaluated using the visual analog scale, Oswestry Disability Index, and Macnab criteria. Univariate analysis explored the relationship between postoperative MCs and pain, while subgroups investigated the associations between postoperative efficacy, recurrence, and MCs type and area. Results One‐year follow‐up revealed that the probability of MCs postsurgery was 24.8%. Patients with postoperative MCs had significantly lower pain scores compared with the control group (p < 0.05). Univariate analysis indicated that the type and area of postoperative MCs were risk factors for poor outcomes in PELD patients (p < 0.05). During the 1‐year follow‐up, recurrence rates in the no‐MCs and MCs groups were 3.8% and 9.6%, respectively (p < 0.05). Univariate analysis concluded that the area of postoperative MCs was a risk factor for PELD recurrence. Conclusion The postoperative MCs, as a risk factor, may have a detrimental effect on the surgical efficacy and short‐term recurrence of LDH following PELD based on a large sample. Furthermore, the harmful effect is affected by the area and type of the postoperative MCs.